1973
DOI: 10.1073/pnas.70.6.1772
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic System in Parthenogenetic Strains of Drosophila mercatorum

Abstract: Five parthenogenetic laboratory strains of Drosophila mercatorum have been examined for their mode of diploidization in the eggs of females. Diploidization occurs either by pronuclear duplication leading to complete homozygosity or by nuclear fusion. If the latter occurs between pronuclei from different secondary oocytes, heterozygosity can be maintained. Each of the five strains shows some nuclear fusion and three show significantly different amounts, ranging from about 21% to less than 1%. Even in strains wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 6 publications
2
37
0
Order By: Relevance
“…Although some sexual females seem capable of parthenogenetic reproduction when males are unavail-253 able (Carson, 1967;Templeton et a!., 1976;Templeton, 1982), modification of gametogenesis without depression of fertility and stable development may be difficult obstacles to overcome during initial stages of parthenogenesis (Moritz et al,1 989a). These genetic constraints may account for the rarity of parthenogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Although some sexual females seem capable of parthenogenetic reproduction when males are unavail-253 able (Carson, 1967;Templeton et a!., 1976;Templeton, 1982), modification of gametogenesis without depression of fertility and stable development may be difficult obstacles to overcome during initial stages of parthenogenesis (Moritz et al,1 989a). These genetic constraints may account for the rarity of parthenogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In Drosophila melanogaster as in most other member of this genus, parthenogenetic reproduction has never been reported (Stalker 1954;Murdy and Carson 1959;Carson 1967). Since syngamy, per se, does not seem a prerequisite at least to early embryogenesis (Zaloker et al 1975;Santamaria and Gans 1980;Santamaria 1983), some sperm factor not contained in the nucleus, may be implicated in egg activation of these obligatory bisexual species.…”
mentioning
confidence: 99%
“…This appears quite low, but 'it must be noted that this is a rate comparable to that obtained in rthe natural populations . of Dro, sophila mercatorum, the species in which several parthenogenetically reproducing lines have successfully been established (Carson 1967;Templeton et a1.1976) . An attempt to find the impaternate females that can reproduce gynogenetically has brought about one such line, tentatively named gyn-F9,.…”
mentioning
confidence: 99%
“…In the route from tychoparthenogenesis, an increase in the opportunity of successful oviposition by unmated females will be an important condition, because it should select for the capacity of parthenogenetic reproduction. For example, some studies using bisexual Drosophila have shown that the ability of thelytokous reproduction can gradually be improved through selection experiments for unfertilized females that reproduce parthenogenetically (Stalker 1954;Carson 1967;Kramer and Templeton 2001). As in those experiments, replicated occurrence of maleless colony initiation might provide the condition for promoting the ability of parthenogenetic reproduction in R. speratus.…”
Section: Discussionmentioning
confidence: 99%